Revision of the African Neoperla Needham, 1905 (Plecoptera: Perlidae: Perlinae) based on morphological and molecular data - Zwick, Peter; Zwick, Andreas (Zootaxa, 2023)
Adults of the African species of the genus Neoperla Needham, 1905 (Plecoptera: Perlidae: Perlinae) are revised, and 82 valid species are recognised. Of the original 29 named species, 14 valid ones are redescribed from types, nine lectotypes are designated, and nine new synonymies are proposed. Sixty-two new species are named, and several additional new species only known from material insufficient for formal description are listed. There are one unavailable nomen nudum and three doubtful names. Diagnostic morphological traits of the recognised species are described and illustrated in detail where available of males, females, and eggs. Dichotomous keys to all species are provided. Mitochondrial DNA-data of 71 species-group taxa are available, which permits reliable association of sexes and minimises the risk of synonymies between species known from only one sex. Importantly, this includes DNA sequences from 50 holotypes. The DNA-data will also permit future monitoring with eDNA sequencing and identification of nymphs, which are probably important but so far unidentifiable bioindicators in streams. The genus Neoperla occurs largely in the northern hemisphere and in Africa, where it is restricted to the Ethiopian region south of the Sahara but unknown from Madagascar. A single specimen not clearly distinct from a widespread mainland species was taken on Comoro Island. All African species are endemic, but one African species group has a few outlying members in Asia. The Asian N. montivaga-group is not known from Africa. The following new species are described and named: N. aethiopica n. sp., N. amoena n. sp., N. angolana n. sp., N. bareensis n. sp., N. bella n. sp., N. benti n. sp., N. beta n. sp., N. bipolaris n. sp., N. biserrata n. sp., N. brachyphallus n. sp., N. caeleps n. sp., N. cataractae n. sp., N. claviger n. sp., N. coffea n. sp., N. costata n. sp., N. crenulata n. sp., N. crustata n. sp., N. decorata n. sp., N. dianae n. sp., N. dolium n. sp., N. dundoana n. sp., N. duodeviginti n. sp., N. erinaceus n. sp., N. excavata n. sp., N. filamentosa n. sp., N. funiculata n. sp., N. gibbosa n. sp., N. gordius n. sp., N. heideae n. sp., N. ivanloebli n. sp., N. juxtadidita n. sp., N. kalengonis n. sp., N. larvata n. sp., N. lineata n. sp., N. luhohonis n. sp., N. massevensis n. sp., N. multiserrata n. sp., N. muyukae n. sp., N. nichollsi n. sp., N. occulta n. sp., N. orthonema n. sp., N. pallidogigas n. sp., N. panafricana n. sp., N. pickeri n. sp., N. pilulifera n. sp., N. pirus n. sp., N. planidorsum n. sp., N. plicata n. sp., N. proxima n. sp., N. pusilla n. sp., N. rostrata n. sp., N. sambarua n. sp., N. sassandrae n. sp., N. schuelei n. sp., N. serrula n. sp., N. simplex n. sp., N. socia n. sp., N. sorella n. sp., N. spaghetti n. sp., N. spectabilis n. sp., N. spironema n. sp., N. tangana n. sp., N. tansanica n. sp., N. usambara n. sp., and N. vicina n. sp..